INFLUENCE OF INSTAGRAM SHOP FEATURE ON PURCHASE INTENTION OF INSTAGRAM USERS - Christano, Dillon; Putra, Nicolaus Surya Anggara; Sujatmiko, Abraham Teguh Tirta; Sukmaningsih, Dyah Wahyu (JURSIMA, 2023)
This study aims to determine what factors influence consumers in using one of the features in Instagram, namely Instagram Shop. The researcher used the data collection method in the form of a survey where 400 respondents filled out the questionnaire. For the data analysis method, the researcher uses the PLS-SEM method and the Smart PLS application where Smart PLS is an application that uses data processing calculations on the PLS-SEM basis. PLS-SEM is a methodology that is accepted by many disciplines. Of the accepted hypothesis, only 3 and all three are interconnected, Interactivity can affect a person's desires and it can be called Hedonic Motivation. If you have high Hedonic Motivation, the desire to buy can be helped by perceived usefulness, where technology is useful for users when shopping. So the researchers concluded that this feature is actually pretty good and helps stores promote their wares, but is rarely used on Instagram Shop.